Communication of Disease Risk: Persuasive Appeal of Messages in Airport Banners - Ting, Su Hie; Jerome, Collin (2017)
Various factors, notably health beliefs, knowledge of the disease and demographic characteristics have been found to influence public receptivity to disease risk information and their likelihood to perform actions to reduce risk. Research has shown that receptivity to disease risk messages is influenced by the framing of the messages. The health risk messages can be framed to appeal to logic, emotion or credibility of information source – referred to as the rhetorical appeals of logos, pathos and ethos respectively. This study examined the framing of disease risk messages in airport banners to identify persuasive strategies used by the Ministry of Health Malaysia to elicit health preventive behaviour. The banners with disease risk messages for Zika, Hand, Foot and Mouth Disease, Ebola Virus Disease, and Middle East Respiratory Syndrome-Coronavirus Disease were analysed to find out how appeals to logos, pathos and ethos were used to induce fear of susceptibility to the diseases and to prompt preventive behaviour. The analysis revealed that the logos appeal was the most popular as the banners were very informative with mostly information on symptoms and preventive measures. These messages were conveyed through photographs to cater to more visually oriented audiences. There was an obvious absence of appeals to pathos and ethos in the banners. From the perspective of persuasion, the disease risk messages in the airport banners may not achieve their purpose because they do not evoke an emotional response to motivate them to take recommended actions.